Imazighen of France; articulations of an indigenous diaspora. Issue 9 (4th July 2022) - Harris, Jonathan
ABSTRACT: Indigenous diasporas are an emerging social and political phenomenon, and conceptually offer a productive avenue for critical research in the study of ethnicity and migration. The politics of Indigenous peoples in diaspora have not received enough scholarly attention, and this article seeks to respond by examining how indigeneity is articulated by the many Amazigh (non-Arab North African) cultural associations of France. Drawing on Stuart Hall's articulation theory, this article contributes a nuanced approach to the relational concept of indigeneity, exploring four key ways in which disparate subjectivities are articulated with indigeneity in the discourse and practices of the diasporic Amazigh movement. Firstly, diaspora Imazighen articulate with the Global Indigenous Movement. Secondly, they position themselves and their homeland populations as colonised people. Thirdly, they perform cultural authenticity within their project of cultural and linguistic revitalisation. Lastly, they practice a village territoriality that articulates with indigeneity by privileging rurality and pre-colonial political institutions. These diaspora articulations are argued to produce a pro-indigenous, anti-essentialist discourse, which highlights the relational nature of indigeneity.